Implementation of multicultural values in social studies learning at Junior High School Mukhtar Syafa’at - Irawan, Ari; Banowati, Eva; Mustofa, Moh Solehatul (Universitas Negeri Semarang, 2022)
A multicultural school environment makes it easier for students to understand multicultural values. Still, on the other hand, it provides difficulties for students, such as the adaptation process that is not easy due to background differences. This article examines the inculcation of multicultural values in social studies learning. It also discusses the actualization of multicultural values in students' social attitudes. This study also analyses the role of the social environment in supporting the actualization of multicultural values by students. The qualitative approach used is a collective case study design. The results showed that teachers had difficulties making various learning methods and media in the planning stages of social studies learning. At the implementation stage, there were problems with insufficient school infrastructure, and in the evaluation, many students violated the school. Language actualization is going well. Students learn each other's language, some students have difficulty adapting to ethnicity, and a form of cultural actualization is holding an endog parade. The social environment's role is essential in actualizing multicultural values by students. Through multicultural learning, it is expected that students can behave by the multicultural values contained in society.